2020
DOI: 10.1101/gr.267328.120
|View full text |Cite
|
Sign up to set email alerts
|

Global regulatory features of alternative splicing across tissues and within the nervous system of C. elegans

Abstract: ServiceEmail Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article -sign up in the box at the object identifier (DOIs) and date of initial publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 99 publications
2
8
0
Order By: Relevance
“…Mammalian microexons tend to be frame preserving (multiples of 3 nt), such that inclusion or skipping of the microexon does not cause translational frameshifts. We likewise find that PRP-40regulated microexons show a strong preference for frame preservation (Figure 5C), in agreement with recent work on all detectable C. elegans microexons (Koterniak et al, 2020). We also tested whether the PRP-40-regulated microexons we identified are present in existing gene annotations and found that a substantial minority of microexons (30%) were previously unannotated, and a small number (4%) were previously annotated but considered constitutive exons (Figure 5D).…”
Section: Prp-40-regulated Microexons Define a Network Of Neuronal Transcriptssupporting
confidence: 90%
“…Mammalian microexons tend to be frame preserving (multiples of 3 nt), such that inclusion or skipping of the microexon does not cause translational frameshifts. We likewise find that PRP-40regulated microexons show a strong preference for frame preservation (Figure 5C), in agreement with recent work on all detectable C. elegans microexons (Koterniak et al, 2020). We also tested whether the PRP-40-regulated microexons we identified are present in existing gene annotations and found that a substantial minority of microexons (30%) were previously unannotated, and a small number (4%) were previously annotated but considered constitutive exons (Figure 5D).…”
Section: Prp-40-regulated Microexons Define a Network Of Neuronal Transcriptssupporting
confidence: 90%
“…The differentially expressed isoforms with similar change using R package MFUZZ 80 . The 200 bp sequence of upstream and downstream intron flanking alternative exon was extracted using bedtools (version 2.30.0), and the enriched motifs were analysed modified from the previous study using HOMER findMotif.pl script with parameters: ‐len 6,8,10,12 81 . The significantly AS events were selected as regulated events, while the other events were selected as background events.…”
Section: Methodsmentioning
confidence: 99%
“…In the nervous system, efforts to profile neuron-type transcriptomes began nearly two decades ago (ZHANG et al 2002), and have recently cumulated to the CeNGen initiative , which aims to establish a complete gene expression atlas for each neuron from larvae to adults. While conventional bulk RNAseq using dissociated and sorted neurons is a proven success (TAYLOR et al 2019), recent implementation of TRAP-seq (Translating Ribosome Affinity Purification) has uncovered neuronal-type mRNA splicing events (KOTERNIAK et al 2020). In combination with forward genetic screens using elegantly designed reporters that J o u r n a l P r e -p r o o f 8 detect alternative splicing in vivo (THOMPSON et al 2019), there is a greater anticipation to advance mechanistic understanding.…”
Section: Building Single-cell Molecular Expression Atlasmentioning
confidence: 99%